Gold Nanoislands Chip for Laser Desorption/Ionization (LDI) Mass Spectrometry - Noh, Joo-Yoon; Kim, Jo-Il; Chang, Young Wook; Park, Jong-Min; Song, Hyun-Woo; Kang, Min-Jung; Pyun, Jae-Chul (KOREAN BIOCHIP SOCIETY-KBCS, 2017)
Gold nanoislands chip were developed as a solid matrix for the analysis of small molecules using laser desorption/ionization time-of-flight (LDI-ToF) mass spectrometry substituting the organic matrices which usually produce strong noise at low mass to-charge ratio range (m/z <500). Gold nanoislands were simply prepared by (1) deposition of gold layer on highly P-doped silicon substrate followed by (2) heating. Physical properties-of the gold nanoislands were analyzed by scanning electron microscope (SEM), atomic force microscopy (AFM) analysis to characterize the morphology, diameter, thickness, and surface density of the nanoislands which were comparatively analyzed in conjunction with LDI-ToF mass spectrometry. In this work, optimal size of the nanoislands were selected for LDI-ToF mass spectrometry, and gold nanoislands chip were applied to the quantitative and simultaneous detection of small analytes (amino acids) with various chemical and physical properties (polar, nonpolar, acidic, and basic).
Keywords: SURFACE-PLASMON RESONANCE; PHOTOCATALYTIC ACTIVITY; SOLID-MATRIX; SALDI-MS; NANOPARTICLES; IONIZATION; DESORPTION; FILMS; MOLECULES; PEPTIDES